Notation - Akademie der Künste, Berlin (Berlin : Akademie der Künste, 2007)
Andre, Carl ; Arakawa, Shusaku ; Artaud, Antonin ; Benjamin, Walter ; Bochner, Mel ; Broodthaers, Marcel ; Buckminster Fuller, Richard ; Cage, John ; Forsythe, William ; Hejduk, John ; Kahn, Louis ; Kiesler, Friedrich ; Kubelka, Peter ; LeWitt, Sol ; Marey, Etienne-Jules ; Martin, Agnes ; McCall, Anthony ; McCollum, Allan ; Moholy-Nagy, Laszlo ; Schoenholtz, Michael ; Taylor, Al ; Varèse, Edgard ; Xenakis, Iannis ; Zimmermann, Bernd Alois
Duits, engels
Exhibition "Notation", Akademie der Künste Berlin, 21.09.2008 - 16.11.2008
boek